Analysis Factors Affecting the Low Coverage of Tetanus Toxoid Immunization in Pregnant Women at Hutabaginda Health Center Tarutung District Tapanuli Utara District In 2022 - Nurlima N. Nababan; Wisnu Hidayat; Johansen Hutajulu (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Tetanus is a life-threatening bacterial infection due to wound contamination with Clostridium tetani and is characterized by muscle spasms and dysfunction of the autonomic nervous system. The study aimed to analyze the factors that influence the low coverage of tetanus toxoid immunization in pregnant women at the Hutabaginda Health Center, Tarutung District, North Tapanuli Regency, in 2022. Quantitative research method with a cross-sectional approach. The research was conducted in the Hutabaginda Health Center, Tarutung District, North Tapanuli Regency, from November 2022 to March 2023. The study population consisted of 150 pregnant women. The sampling technique used was the probability sampling technique. In probability sampling, the number of samples is 109 pregnant women. The bivariate test uses the Chi-Square Test, and the multivariate test uses the Linear Regression Test. The results showed that there was a relationship between the age of pregnant women and the low coverage of Tetanus Toxoid immunization (p-value = 0.002), there was a relationship between the education of pregnant women and the low coverage of Tetanus Toxoid immunization (p-value = 0.003), there was a relationship between the parity of pregnant women and the low coverage of Tetanus Toxoid immunization (p-value = 0.007), there was a relationship between the knowledge of pregnant women and the low coverage of Tetanus Toxoid immunization (p-value = 0.002), there was a relationship between the attitude of pregnant women and the low coverage of Tetanus Toxoid immunization. tetanus toxoid (p-value = 0.006), and there is a relationship between family support of pregnant women and low coverage of tetanus toxoid immunization (p-value = 0.006) at the Hutabaginda Health Center, Tarutung District, North Tapanuli Regency in 2022. The most dominant factor for pregnant women not to be immunized against tetanus toxoid is the knowledge factor, with a significant value of 0.02 <0.05. Recommendations for pregnant women to take advantage of health facilities to get pregnancy health services by participating in tetanus toxoid immunization. Keywords: Coverage, Immunization, Pregnant Women, Tetanus Toxoid